Abordagem da paleontologia nos livros didáticos de biologia do ensino médio - Alonço, Mayra (2015)
The textbook is one of the main pedagogical tools used by Basic Education teachers to assist in the education of the student. Discussions about the quality of the textbooks have provoied significant changes in editorial production, showing the necessity of quality parameters creation to guide the responsible teachers improve their choices for approving the collections. Paleontology is recommended by PCNs as an integral theme of the Biology content in high school, it contributes to understanding the origin and evolution of life on earth and refers to the composition of the atmosphere, geography and climate changes over geological time. In this sense, this research investigated the Paleontology content inserted in the following collections of textbooks Biology :Novas Bases da Biologia – Editora Ática S/A , Conexões com a Biologia -Editora Moderna Ltda, Ser protagonista – Edições SM Ltda, Biologia – Editora - Saraiva AS Livreiros e Editores, Biologia – Editora AJS Ltda. These collections were recommended by the Ministério de Educação e Cultura (MEC) based on the Programa Nacional de Livros Didáticos (PNLD), Fundo Nacional de Desenvolvimento da Educação (FNDE) and also on the Parâmetros Curriculares Nacionais (PCNs) to choose the current collection in a public high schools in 2015. As analysis method was used the PNLD Guide and the content was analyzed the acoording of Bardin (2006) proposal.